DISKURSUS TAAT PEMERINTAH PERSPEKTIF SAYYID QUTB DALAM TAFSIR FI DZILAL AL-QUR’AN : (Studi Pembacaan QS. al-Nisa’ (4): 59) - Hudri, Misbah (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2024)
This paper discusses the interpretation of QS. al-Nisa’ (4): 59 by Sayyid Qutb in his interpretation of fi Dzilal Al-Qur'an. One of the prolific scholars, who had an influential mind, was also involved in practical practice. His interpretation is often referred to as the interpretation of barakah. This is included in the type of research that is qualitative. Using a descriptive-analytic data processing system with work instruments that are library research. This study uses Critical Discourse Analysis (CDA) or Fairclough's critical discourse analysis, which confirms the relationship between language use and social reality dialogue and interaction. Sayyid Qutb's interpretation of the QS. al-Nisa’ (4): 59, explains a justification in a state with an Islamic dimension. According to him, only one form of state can support the Islamic government, namely an Islamic state (dar al-Islam). The model of government must be following Islamic law. If not then he believes in the scared. As for obeying ulil amri is a continuation of obeying Allah and the Messenger. Obedience to the government or ulil amri stated in the interpretation contains a mandate that must be enforced. The view of the Qur'an states that obedience to the leader is an indication of faith. Sayyid Qutb's interpretation gave birth to his unique understanding. Even the context he faced at that time. The conditions behind it also had a considerable influence on it.